Domestic Macroeconomic Adjustment to Oil Price Shocks Under Different Exchange Rate Regimes in Malaysia (Malaysian Management Journal, 2007)
This study examined the insulation properties of flexible exchange rate regime and fixed exchange rate regime in response to the oil price shocks in Malaysia. A monthly time series data for the period 1980- 2005 was used to examine whether the response of output, exchange rate and price levels to the oil price shocks were different across the exchange rate regimes. For this purpose, this study employed the structural vector autoregressive model. Empirical results indicated that the short-run output responses to the oil price shocks are smoother under the flexible exchange rate regime compared to the situation under the fixed exchange rate regime.